The Dynamics of Internal Communication Co-Orientation in Family Business Startups: A Case Study of Intergenerational Communication at the Padel Side - Zahra Shafwah Alaydrus; Azwar Azwar (Eduvest - Journal of Universal Studies, 2025)
This study analyzes the internal communication co-orientation dynamics at a family business startup, The Padel Side, amidst the generational gap between Millennial management and Gen Z staff. Using an explanatory qualitative case study method (Yin, 2018) and Organizational Co-orientation Theory (Taylor, 1993), the research identifies four fundamental distortions: (1) a false consensus effect at the management level that creates a decision-making "black box," failing to translate into clear operational instructions; (2) failure in objectifying the meaning of "proactivity," where leaders view it as a moral/loyalty standard, while staff perceive it as a systemic risk leading to "freezing"; (3) digital text pathology through WhatsApp that triggers semantic ambiguity and hermeneutic anxiety among staff due to the loss of non-verbal cues; and (4) kinship stratification creating power asymmetry between family staff (symmetrical relationship) and non-family staff (complementary relationship/self-censorship). The study concludes that the codification of written SOPs and the implementation of hybrid communication protocols are crucial to mitigate message distortion and agency crisis within the organization.